Clinical consequences of arteriovenous graft infection:a single-center study - BIAN Xue-qin; LUO Yuan; WU Xian; GU Chun-feng; ZHOU Wen-jing; YE Hong (Linchuang shenzangbing zazhi)
Objective The purpose of this study was to perform a retrospective analysis on clinical efficacy of different therapies for arteriovenous graft(AVG) infection.Methods A total of 29 AVG infection patients in the Second Affiliated Hospital of Nanjing Medical University from October 2014 to October 2019 were analyzed retrospectively in the study.The clinical features after AVG infection and the long-term prognosis of different therapies were observed.Results There were 33 AVG cases occurred in 29 patients with an infection incidence of 6.3%.Their mean age was 56 years and 58.6% were female.Among these cases,the ones of AVG infection in the forearm accounted for 72%,the resting ones were AVG infection in the upper arm.After infection,7 patients(24.3%) underwent conservative therapy,12 ones(41.4%) partial resection and interposition,7 ones(24.3%) subtotal resection,and 3 ones(10.3%) total resection.The infection mainly occurred at the puncture site for the AVG(62.1%).The pathogens obtained through microbial culture were mainly Staphylococcus aureus in 51.8% of specimens.The recurrence rate of AVG infection was 13.9%.Chi-square test showed,the patients had statistically significant differences in white blood cells,procalcitonin,pathogen infection,fever and local skin injury in the infection segment(P<0.05).However,Logistics multiple regression analysis showed that these infectious indices,and sex,age,diabetes and surgical mode did not affect cumulative patency(P>0.05).Conclusions AVG infection is the most serious complication of AVG.The surgical mode should be decided according to clinical manifestations and infection indices.